2016
DOI: 10.1021/acs.jmedchem.6b00505
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Rational Design of Natural-Product-Derived 2-Phenyl-3,4-dihydro-2H-benzo[f]chromen-3-amine Analogs as Novel and Potent Dipeptidyl Peptidase 4 (DPP-4) Inhibitors for the Treatment of Type 2 Diabetes

Abstract: Starting from the lead isodaphnetin, a natural product inhibitor of DPP-4 discovered through a target fishing docking based approach, a series of novel 2-phenyl-3,4-dihydro-2H-benzo[f]chromen-3-amine derivatives as potent DPP-4 inhibitors are rationally designed utilizing highly efficient 3D molecular similarity based scaffold hopping as well as electrostatic complementary methods. Those ingenious drug design strategies bring us approximate 7400-fold boost in potency. Compounds 22a and 24a are the most potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…Hao et al discovered two series of potent and selective EGFR inhibitors againstL858R/T790 M resistance mutation by scaffold hopping with SHAFTS . Li et al discovered and designed a series of novel and potent DPP‐4 inhibitors for treating type 2 diabetes mellitus (T2DM) based on a natural product lead using SHAFTS . Wang et al used SHAFTS method for scaffold hopping and discovered a potent inhibitor of human copper trafficking for the treatment of cancer …”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Hao et al discovered two series of potent and selective EGFR inhibitors againstL858R/T790 M resistance mutation by scaffold hopping with SHAFTS . Li et al discovered and designed a series of novel and potent DPP‐4 inhibitors for treating type 2 diabetes mellitus (T2DM) based on a natural product lead using SHAFTS . Wang et al used SHAFTS method for scaffold hopping and discovered a potent inhibitor of human copper trafficking for the treatment of cancer …”
Section: Experiments and Discussionmentioning
confidence: 99%
“…From the comparison of DPP-4 level between child patients and normal children, it was found that DPP-4 level of child patients with T1DM significantly increased, according to the feature of insulin absolute shortage for T1DM. In addition, after the treatment with insulin, the DPP-4 level of children with T1DM decreased obviously, so we speculated that it may depend on the function characteristics of DPP-4, which mainly included (1820): i) The function of regulating pancreas β cells and secrete insulin; ii) the unique insulin dependence feature of secreting and regulating blood glucose when glucose is increasing in human body. Therefore, it has a defensive function for pancreas β cells, which can significantly reduce the apoptosis of pancreas β cells and prolong the life span of islet cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…4 Given the clinical success of DPP-4 inhibitors, there has been ongoing interest in the development of drug candidates with longer half-lives that decrease dosing frequency. 5 Such therapies would provide advantages to the patient of improved medication compliance and minimized side effects. In this vein, omarigliptin ( 1 , MK-3102), a highly functionalized long-acting DPP-4 inhibitor, was developed and recently approved for the once-weekly treatment of type 2 diabetes in Japan (Figure 1).…”
Section: Introductionmentioning
confidence: 99%